Measuring burdening effect of Shariah knowledge on sales performance; does work experience matter? A multi-group analysis in the Islamic finance industry - Shamsudheen, Shinaj Valangattil; Mahomed, Ziyaad (International journal of Islamic and Middle Eastern finance and management, 2021)
Purpose This study aims to examine the burdening effect of Shariah knowledge on the sales performance of the salesforce at Islamic financial institutions (IFIs) with special reference to addressing the heterogeneous effects of work experience. Design/methodology/approach A total of 335 samples were collected from the sales professionals of IFIs in Malaysia using a purposive sampling technique and the empirical analysis was conducted with the measures of model fit and bootstrapping technique using partial least square structural equation modeling and multi-group analysis. Findings Empirical results indicate that the burdening effect of Shariah knowledge is evident among salesforce and the magnitude of the impact remains consistent across the groups of salesforces with different levels of work experience. Practical implications Findings suggest respective authorities of IFIs intensify capacity building for their salesforce particularly in the area of Shariah knowledge and nature of underlying Islamic contracts used in the financial products. An insignificant heterogeneous effect of work experience suggests respective authorities that the actions and policy formulations are equally important among the entire salesforce regardless of the number of years of job tenure each salesforce holds. Originality/value As customer awareness and knowledge may be influenced by the information transferred via the IFI employees (especially salesforce in IFIs), any information overload (i.e. additional requirement of Shariah knowledge/features) on the IFI employees may, therefore, negatively influence customer patronage and reduce IFI market share. However, the increased information expectation (i.e. Shariah knowledge/features) on IFI employees and its impact on market share along with the heterogeneous effect of work experience has not been documented before. If a burdening effect of Shariah knowledge is identified, this may be a formidable reason for the slowing growth of Islamic finance.